2011
DOI: 10.1002/path.2895
|View full text |Cite
|
Sign up to set email alerts
|

Notch3 signalling promotes tumour growth in colorectal cancer

Abstract: Increased Notch1 activity has been observed in intestinal tumours, partially accomplished by β-catenin-mediated up-regulation of the Notch ligand Jagged-1. Whether further mechanisms of Notch activation exist and other Notch receptors might be involved is unclear. Microarray data indicated that Notch3 transcript levels are significantly up-regulated in primary and metastatic CRC samples compared to normal mucosa. Moreover, Notch3 protein was expressed at strong/moderate levels by 19.7% of 158 CRC samples analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
73
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 49 publications
5
73
0
Order By: Relevance
“…Previous studies have indicated that Notch signaling is upregulated in CRC (15)(16)(17)(18). However, data regarding the expression of JAG2 protein in CRC tissues is scarce.…”
Section: A B Discussionmentioning
confidence: 99%
“…Previous studies have indicated that Notch signaling is upregulated in CRC (15)(16)(17)(18). However, data regarding the expression of JAG2 protein in CRC tissues is scarce.…”
Section: A B Discussionmentioning
confidence: 99%
“…The activation of Notch 1 signaling appears to sustain the motility, migration and invasion of tumor cells in esophagus squamous cell carcinomas, lingual squamous cell carcinoma, endometrial carcinoma and breast cancer (11)(12)(13)(14)(15). Almost all cases of T cell acute lymphoblastic leukemia (T-ALL), and colorectal, pancreatic and ovarian cancer have been reported to exhibit aberrant Notch 3 expression (6,8,16,17). Our previous study also reported that Notch 3 overexpression was associated with a poor prognosis in NSCLC patients (18).…”
Section: Introductionmentioning
confidence: 84%
“…Using ontology analysis consisting of proliferation, migration, and angiogenesis, we discovered 4 genes that satisfied these 3 biological criteria ( Figure 3, A and B). Among these, JAG1 (which encodes the Notch ligand) was particularly interesting, because activation of Notch signaling is involved in human colon cancer (5,12,13,(33)(34)(35). We also conducted expression microarray profiling of control and GM00637-APEX1 cells.…”
Section: Introductionmentioning
confidence: 99%
“…Given the importance of Jagged1/Notch signaling in colon carcinogenesis (5,12,34,35,38), the involvement of Jagged1 in APEX1-mediated increased tumorigenicity of colon cancer cells was of interest. Additionally, the transcriptional regulation of human Jagged1 has been elusive.…”
Section: Introductionmentioning
confidence: 99%